Spatiotemporal dynamics of citrus huanglongbing spread: a case study - Gasparoto, M. C.G. [UNESP]; Hau, B.; Bassanezi, R. B.; Rodrigues, J. C.; Amorim, L. (Wiley, 2018)
Citrus huanglongbing (HLB) is a severe disease caused by ‘Candidatus Liberibacter asiaticus’ and vectored by Diaphorina citri. In commercial orchards, where the disease is controlled by removal of trees with symptoms and by frequent vector control, epidemics of HLB are mostly driven by primary infections from inoculum sources external to the orchard. It has been previously shown that the density of D. citri populations is usually higher around the edges than the inner sections of HLB-affected citrus orchards. Consequently, diseased trees are also concentrated on the edges of orchards. However, there is a lack of quantitative data on HLB gradient dynamics over long periods of time. The objective of this study was to characterize temporal HLB progress and spatiotemporal gradient dynamics over six years in a large citrus farm where the disease was managed according to standard recommendations. Disease incidence and annual disease progress rates were higher at the citrus blocks closer to the edge than those located around inner sections of the farm. A decreasing logistic function provided a good description of the spatiotemporal dynamics of HLB gradients. A fixed slope of disease gradients was estimated over time and diseased trees were observed up to 1500 m from the orchard border. These results confirm that primary infection is the main factor for the progress of HLB epidemics in an orchard under the recommended three-pronged system management. Therefore, HLB management should be intensified at the blocks located on the edges of the orchards and extended to external sources of inoculum.
Keywords: border effect; Citrus sinensis; dispersal gradients; edge effect; greening; huanglongbing